Inhibitory Effect of Cinobufagin on L-Type Ca2+ Currents, Contractility, and Ca2+ Homeostasis of Isolated Adult Rat Ventricular Myocytes. (25th May 2014) - Li, Pinya; Song, Qiongtao; Liu, Tao; Wu, Zhonglin; Chu, Xi; Zhang, Xuan; Zhang, Ying; Gao, Yonggang; Zhang, Jianping; Chu, Li
Abstract : Cinobufagin (CBG), a major bioactive ingredient of the bufanolide steroid compounds of Chan Su, has been widely used to treat coronary heart disease. At present, the effect of CBG on the L-type Ca 2+ current (I Ca- L ) of ventricular myocytes remains undefined. The aim of the present study was to characterize the effect of CBG on intracellular Ca 2+ ([ Ca 2+ ] i ) handling and cell contractility in rat ventricular myocytes. CBG was investigated by determining its influence on I Ca- L, Ca 2+ transient, and contractility in rat ventricular myocytes using the whole-cell patch-clamp technique and video-based edge-detection and dual-excitation fluorescence photomultiplier systems. The dose of CBG (10 −8  M) decreased the maximal inhibition of CBG by 47.93%. CBG reduced I Ca- L in a concentration-dependent manner with an IC50 of 4 × 10 −10  M, upshifted the current-voltage curve of I Ca- L, and shifted the activation and inactivation curves of I Ca- L leftward. Moreover, CBG diminished the amplitude of the cell shortening and Ca 2+ transients with a decrease in the time to peak (Tp) and the time to 50% of the baseline (Tr). CBG inhibited L-type Ca 2+ channels, and reduced [ Ca 2+ ] i and contractility in adult rat ventricular myocytes. These findings contribute to the understanding of the cardioprotective efficacy of CBG.